KESULITAN-KESULITAN MAHASISWA PLS FIP UNP DALAM MENYUSUN SKRIPSI - Wirdatul Aini (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2014)
This research was motivated by the difficulties experienced by students out of School Education ( PLS ) in the thesis . The purpose of this study is to describe the difficulties student writing his thesis in terms of aspects : ( 1 ) the guidance given faculty , ( 2 ) an understanding of research methodology course material , ( 3 ) writing research reports , and ( 4 ) the availability of facilities such as a book source This research is a descriptive study ekspost facto , which examined according to what the problems are experienced students while now . Population and once gus as the samples of this study were students who were writing his thesis on half July- December 2011. Data collection techniques and tools are questionnaires are questionnaires guidelines . Descriptive data were processed by a percentage formula . The study's findings describe : ( 1 ) students sometimes have difficulty writing his thesis in terms of faculty guidance , ( 2 ) students always have trouble writing his thesis in terms of understanding the course material research methodology , ( 3 ) students sometimes have difficulty writing his thesis on aspects writing research reports , and ( 4 ) students always have trouble writing his thesis in terms of aspects of the availability of facilities , especially the difficulty in understanding the sources of books in foreign languages ​​. Suggestions in this study so that students can increase their motivation to better understand the material research methodology , and the ability to understand the sources of books in foreign languages.